2008
DOI: 10.1080/15574090902913651
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Risks Among Male and Transgender Sex Workers in Pakistan

Abstract: Using data from a qualitative study and a subsequent quantitative survey among 918 male and transgender sex workers (MTSW), we explore the context of multiple risks they face. We show that over one-fifth of MTSW have sex with IDU clients. Combined with high levels of risk behavior and very low levels of risk reduction and knowledge, the extent of sexual networking with men who inject drugs contributes further to the sex workers' health risks. Our findings suggest that isolated interventions with single-risk gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
2
13
2
Order By: Relevance
“…Aggregate condom use was low, consistent with previous studies 17 18 27. However, upon stratification, Quetta respondents reported over a twofold likelihood of condom use.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Aggregate condom use was low, consistent with previous studies 17 18 27. However, upon stratification, Quetta respondents reported over a twofold likelihood of condom use.…”
Section: Discussionsupporting
confidence: 86%
“…Importantly, distinctiveness translated into higher levels of risk behaviours associated with pathogen transmission,18 such as decreased condom use and increased use of psychoactive substances during sex work 18 27. Unlike others, however, we did not find any evidence (at an aggregate level) of increased levels of STI or HIV infection among HSW,18 although stratified analyses revealed that HSW in Multan were more likely to be positive for STIs than MSW.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…HIV prevention among PWID must be made a priority for HIV/AIDS strategies in MENA; and obstacles must be addressed for the provision of comprehensive services and enabling environments for PWID [118]. There is need to review current HIV programs among PWID in light of the emerging epidemics, and to develop service delivery models with embedded links between community-based prevention (needle/syringe exchange programs and condom provision), HIV testing, and treatment (opioid substitution and ART).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, many of these studies include transgender women under the MSW indicator, further confounding interpretation. For example, while Pakistan reported data specifically on the indicator for MSW, the study was focused nearly exclusively on hijras (considered a third gender in India and Pakistan) 25 . UNGASS reports also have limited scope, and not all regions report on MSW as a formal behavioural category: for instance, MSW do not comprise an official HIV risk transmission category in North America.…”
Section: Limitations Of Current Data Hiv Reporting Systems For Mswmentioning
confidence: 99%